Are Ly α emitters segregated in protoclusters regions? - Hough, Tomás (2020)
The presence of neutral hydrogen in the inter-stellar medium (ISM) and inter-galactic medium (IGM) induces radiative transfer (RT) effects on Ly α photons which affect the observability of Lyman alpha emitters (LAEs). We use the GALFORM semi-analytic model of galaxy formation and evolution to analyse how these effects shape the spatial distribution of LAEs with respect to H α emitters (HAEs) around high density regions at high redshift. We find that when a large sample of protoclusters is considered, HAEs showing also Ly α emission (HAEs+LAEs) populate the same regions as those that do not display the Ly α line at z = 2.2. We compare against the protocluster USS1558-003, one of the most massive protoclusters located at z = 2.53. Our results indicate that the strong depletion of HAEs + LAEs present in the high density regions of USS1558-003 may be due to cosmic variance. We find that at z = 2.2 and z = 3.0, RT of the ISM produces a strong decline (30-50 per cent) of the clustering amplitude of HAEs + LAEs with respect to HAEs towards the protoclusters centre. At z = 5.7, given the early evolutionary state of protoclusters and galaxies, the clustering of HAEs + LAEs has a smaller variation (10-20 per cent) towards the protoclusters centre. Depending on the equivalent width and luminosity criteria of the emission-line galaxy sample, the IGM can have a mild or a null effect on galaxy properties and clustering in high density regions.